Effect of Additional Information on Consumer Acceptance: An Example with Pomegranate Juice and Green Tea Blends - Higa, Federica; Koppel, Kadri; Chambers, Edgar, IV (My University, 2017)
Pomegranate Juice (PJ) and Green Tea (GT) products have increased in popularity because of their beneficial health properties. Consumers look for healthier beverages, and rely on labels, claims, and product packaging when choosing a product. The objectives of this study were to determine (1) the sensory profiles and acceptance of PJ and GT blends; (2) whether additional information would have an effect on consumer acceptance; and (3) the total phenolic content (TPC) of the samples. Six PJ and GT blends were evaluated by a descriptive panel in order to explore sensory differences in flavor characteristics. A consumer panel (n = 100) evaluated the samples before and after beneficial health information about the samples was provided to them. The blends that were higher in tea concentration were higher in Green and GT-like flavors, and lower in berry, beet, floral, sweetness, and cherry flavors. The overall liking scores of all of the samples increased after the information was provided to the consumers. The sample highest in PJ and lowest in GT blend was liked the most. In addition, as the samples increased in PJ, the TPC content increased. These results may be of interest to the beverage industry, providing information of consumer liking of beverage blends, and how information on health related claims affects consumer acceptance.
Citation: Higa, F., Koppel, K., & Chambers, E. (2017). Effect of Additional Information on Consumer Acceptance: An Example with Pomegranate Juice and Green Tea Blends. Beverages, 3(3), 30. https://doi.org/10.3390/beverages3030030
Keywords: Consumer; Green Tea; Health; Phenolic Content; Pomegranate Juice